Literature Review: Komplikasi Maternal dan Neonatal Akibat Persalinan Macet - Fitri Yuniarti; Dintya Ivantarina (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Obstructed labor significantly occur in developing countries including Indonesia, contributing to maternal and neonatal health. The burden of obstructed labor and adverse fetomaternal outcomes appears to remain high and is a common challenge. One of them is caused by delays in making decisions regarding referral approval due to lack of information about complications that occur in maternal and neonatal. Therefore, identification of the outcomes of obstructed labor that occurs in maternal and neonatal is very important with the aim of knowing the maternal and neonatal complications resulting from obstructed labor. The method used is a literature study using an online database, namely Pubmed and Google Scholar based on inclusion criteria. The results of this study obtained 13 articles showing maternal complications due to obstructed labor, namely uterine rupture, postpartum hemorrhage, anemia, shock, sepsis, blood transfusion, hysterectomy, bladder rupture and injury, fistula, perineal and cervical lacerations, pelvic floor sequelae, musculoskeletal disorders, genitourinary, postpartum depression and death while fetal complications were sepsis, asphyxia, respiratory distress, meconium aspiration syndrome, seizures, jaundice, stillbirth, perinatal and neonatal death. Prevention of obstructed labor is carried out through a multidisciplinary approach aimed in the short term to identify high-risk cases since pregnancy. In the long term, improving education and better health from health workers for mothers and families related to maternal and neonatal complications due to evidence-based obstructed labor so as not to hesitate in making decisions regarding approval of referral actions so that cases of obstructed labor can be handled on time and do not cause dangerous complications. for mother and baby.